SYMBOLIC CONSTRUCTION IN THE EARLY REPUBLIC: CULTURE, IDENTITY AND TURKISH FOLK MUSIC - Koçer, Burak (Tolga Karaca, 2025)
In the Early Republican Period, the relationship between culture and symbol clearly reveals the strategic significance of Turkish folk music in the construction of national identity. As theorists like White, Sapir, and Gerbner emphasize, culture largely comprises shared symbols and continually reproduces a society’s collective memory, values, and identity. In this context, the folklore studies inspired by Europe in the late Ottoman era also gained the attention of Turkish intellectuals, laying the groundwork for the perception of the “people’s” cultural heritage as the “root source of national culture.” To strengthen national identity, the Early Republican authorities positioned folk music at the center of state-supported policies and launched systematic collection and dissemination efforts via radio broadcasts, People’s Houses (Halkevleri), and conservatories. The “Yurttan Sesler” (Voices from the Homeland) choir served as a symbolic peak of this process, functioning as a model in which selective interventions were made on folk songs and their lyrics were rearranged in accordance with the “national spirit.” Traditional instruments like the bağlama, despite the winds of modernization, reclaimed their place on stage in pursuit of a “national sound.” Through this “selective invention of tradition,” folk music evolved from a mere aesthetic or folkloric element into a potent symbol that bolstered political legitimacy, collective memory, and social belonging. Thus, in the modern nation-state building of the Early Republican era, one can see how cultural symbols were effectively employed through folk music. Today, folk music continues to hold a central position in discussions of identity, culture, and tradition. © 2025, Tolga Karaca. All rights reserved.
ERKEN CUMHURİYET’TE SEMBOLİK İNŞA: KÜLTÜR, KİMLİK VE TÜRK HALK MÜZİĞİ
Keywords: culture; national spirit; social belonging; symbol; Turkish folk music